2016
DOI: 10.1007/s10557-016-6689-7
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone Compared with Lidocaine for Out-Of-Hospital Cardiac Arrest with Refractory Ventricular Fibrillation on Hospital Arrival: a Nationwide Database Study

Abstract: The present nationwide study suggested that there was no significant difference in the rate of survival to hospital discharge between cardiogenic OHCA patients with persistent ventricular fibrillation on hospital arrival treated with amiodarone or lidocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
0
18
1
1
Order By: Relevance
“…We compared the rates of survival to discharge among cardiogenic OHCA patients with persistent VF/pVT on hospital arrival following treatment with either amiodarone or nifekalant [28], and amiodarone or lidocaine [29]. …”
Section: Analyses Of Data From a Japanese Nationwide Database: Comparmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the rates of survival to discharge among cardiogenic OHCA patients with persistent VF/pVT on hospital arrival following treatment with either amiodarone or nifekalant [28], and amiodarone or lidocaine [29]. …”
Section: Analyses Of Data From a Japanese Nationwide Database: Comparmentioning
confidence: 99%
“…In the study that compared amiodarone and lidocaine [29], we identified 3,951 patients from 795 hospitals who experienced cardiogenic OHCA and had refractory ventricular fibrillation on hospital arrival. The patients were categorized into amiodarone ( n  = 1,743) and lidocaine ( n  = 2,208) groups, from which 801 propensity score‐matched pairs were generated.…”
Section: Analyses Of Data From a Japanese Nationwide Database: Comparmentioning
confidence: 99%
“…We retrospectively evaluated data from the Japanese Diagnosis Procedure Combination (DPC) database, which is a nationwide in-hospital patient administrative database [28][29][30]. The DPC database includes administrative claims and discharge abstract data for all patients (including OHCA patients who die in the emergency room) discharged from more than 1,000 participating hospitals, covering all 82 academic hospitals and more than 90% of all tertiary-care emergency hospitals in Japan.…”
Section: The Roc-alps Studymentioning
confidence: 99%
“…The DPC database includes administrative claims and discharge abstract data for all patients (including OHCA patients who die in the emergency room) discharged from more than 1,000 participating hospitals, covering all 82 academic hospitals and more than 90% of all tertiary-care emergency hospitals in Japan. The database includes the following information for each patient, recorded using a uniform data submission form: age, sex, medical procedures (e. g., defibrillation, therapeutic hypothermia, and percutaneous coronary angiogram/ intervention), daily records of all drugs administered and devices used (e. g., amiodarone, nifekalant, lidocaine, extracorporeal membrane oxygenation [ECMO], and intra-aortic balloon pumping [IABP]), length of hospital stay, and discharge status (home, transfer to another hospital, death in the emergency room, or death after admission) [28][29][30].…”
Section: The Roc-alps Studymentioning
confidence: 99%
See 1 more Smart Citation